Adaptive response in hepatitis B virus infection. Issue 5 (27th March 2014) - Loggi, E.; Gamal, N.; Bihl, F.; Bernardi, M.; Andreone, P.
Summary Hepatitis B virus (HBV) is a major cause of acute and chronic liver inflammation worldwide. The immune response against the virus represents a key factor in determining infection outcome, in terms of both viral clearance and the perpetuation of liver damage. Significant advances have recently been achieved regarding the functions of antiviral CD8+ T cells, leading to a better understanding of their abnormalities during chronic infection as well as the pathways to be manipulated to reverse the immune impairment of chronic infection. In this review, we aimed to analyse the patterns of adaptive immunity that develop during acute infection and the profiles in chronic infection. In addition to CD8+ T cells, which are the best‐described subset to date, we reviewed and commented on the direct and indirect roles of CD4+ T cells and B cells.